2011
DOI: 10.3415/vcot-10-03-0038
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of stair ascent in healthy dogs

Abstract: All joints of the pelvic limb undergo a greater joint motion to ascend stairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The traditional method utilized for analyzing canine stifle kinematics involves attaching reflective markers to the overlying skin of tissue landmarks with movement captured by digital cameras [58]. These studies, while non-invasive, do not provide precise data regarding movement of the underlying bones; instead these studies only yield general information on the angles and velocities of femorotibial flexion-extension movement.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional method utilized for analyzing canine stifle kinematics involves attaching reflective markers to the overlying skin of tissue landmarks with movement captured by digital cameras [58]. These studies, while non-invasive, do not provide precise data regarding movement of the underlying bones; instead these studies only yield general information on the angles and velocities of femorotibial flexion-extension movement.…”
Section: Introductionmentioning
confidence: 99%
“…The exercise started on the 14th day after the surgical correction because AROM exercise required the greater strength of muscle (Millis and Levine, 2014). We used trotting gait in this study because it provided greater joint excursion of each joint approximately five degree except in stifle joint can be increased approximately 20 degrees of motion as compared with walking (Durant et al, 2011). Therefore, we would like to investigate the greater excursion of trotting when using non-slipping socks.…”
Section: Chapter V Discussionmentioning
confidence: 99%
“…The AROM of forelimbs and pelvic limbs are investigated during ascending the stair compared with trotting on ground surface. The study found that walking on ramp or ascending stair provided increase in range of motion of forelimbs and pelvic limbs (Millard et al, 2010;Durant et al, 2011;Carr et al, 2013). Swimming provided greater range of motion of the stifle and hip joints compared with walking in dogs undergone surgical correction of cranial cruciate ligament rupture (Marsolais et al, 2003).…”
Section: Importance and Rationalementioning
confidence: 94%
See 2 more Smart Citations